STRATEGI PROMOSI LOYALTY PROGRAM MY PERTAMINA YANG DILAKUKAN OLEH PT PERTAMINA (PERSERO) TAHUN 2018 - Salsabila Heryadi, Gina (Jurnal Visi Komunikasi, 2019)
Marketing is currently growing rapidly. Promotion is very important to market a product so that customers know that the product is worth buying. A mature strategy is needed to promote a product. promotion strategies for successfully marketing company products to the public quickly and on target. Based on this, the authors focus on research, namely "How is the My Pertamina Loyalty Promotion Strategy conducted by PT Pertamina (Persero) in 2018?". My Pertamina is a loyalty program that was formalized by PT Pertamina (Persero). The strategy undertaken by PT Pertamina (Persero) in promoting the My Pertamina program is by segmenting, targeting and positioning, and implementing a promotion mix. The results of this study are My Pertamina’s strategy is divided into two parts, namely in terms of operations and marketing.